The Peer Feedback Strategy in Teaching Writing - Mohammad Febryanto; Danny Gandana Nugraha (Jurnal Bahasa Inggris Terapan, 2018)
Peer feedback is a strategy that enables the students to trigger the writing learning process, and this study was conducted to figure out the aspects involved in the peer feedback. The research design is a case study through a qualitative and descriptive method based on questionnaire and observations involving 58 students of the 3-year Diploma of Business Administration Study Program. The result shows that the focus they took was the grammatical aspect which implies their own barrier.